VR haptics for glovebox operations training - Hornsby, Jared H.; Arnwine, Austin; Stowe, Ashley; Lin, Mary; Mason, Chris; Eakins, Mike; Veller, Devon; Mendoza, Christian; Metcalf, David; Oriaifo, Victor; Dunar, Andrew; Crockett, Bob (Frontiers in Virtual Reality, 2025)
Virtual environments allow training of situations and scenarios that are hazardous and impractical to train for in the physical environment. This paper aims to illustrate the utility of a virtual reality glovebox with haptic feedback as an effective training tool for glovebox operations. Twenty-four participants (16 males, 8 females) volunteered to participate in this study. Each participant completed one trial that consisted of three counter-balanced environments (physical training glovebox, virtual reality with haptic feedback, and virtual reality with handheld controllers), followed by a 10-minute recovery phase after each environment. Each glovebox environment had a near identical glovebox task where participants removed, sorted, and then returned simulated hazardous material to a cannister. Median time to completion (TTC), number of errors, ratings of perceived exertion (RPE), and perceived recovery status scale (PRSS) were calculated to describe the difference in glovebox environment performance. Median TTC was near double for the virtual glovebox environments versus the physical training glovebox environment. Median number of errors were near zero for all environments. Median RPE and PRSS were relatively similar across environments. The results of this study conclude that while the TTC for the physical training glovebox was significantly quicker than the virtual environments, the accuracy of training, RPE, and PRSS were reasonably similar across all environments. Furthermore, given that there is little opportunity and resources for glovebox operators to train this type of task on a regular basis in a physical glovebox, having the opportunity to train this task in a virtual environment provides great value to increase their knowledge, skills, and safety.